2020
DOI: 10.3390/molecules25122780
|View full text |Cite
|
Sign up to set email alerts
|

Tocopheryl Succinate-Induced Structural Changes in DPPC Liposomes: DSC and ANS Fluorescence Studies

Abstract: Recent studies show that alpha-tocopheryl succinate (TS) exhibits selective toxicity against cancer cells. In this study, we investigated the effect of TS’s presence on the physico-chemical and structural properties of DPPC liposomes using fluorescence parameters (intensity, lifetime, and position of emission maximum) of 1-anilino-8-naphtalene sulphonate (ANS), differential scanning calorimetry (DSC) and zeta potential methods. Increasing the TS presence in the DPPC gel phase produced ANS fluorescence enhancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 55 publications
2
16
0
Order By: Relevance
“…In DSC measurements, the increasing presence of tocopherols always led to broadening of ΔT 1/2 , progressively decreasing T m and diminishing ΔH m and cooperativity, together with the simultaneously formed new bands, thus indicating that the structural changes in the liposomes were induced by the presence of tocopherols, leading to a fluidization process at lower temperatures. Our studies in DPPC have shown that the presence of α-T at low concentration affects the membrane’s physicochemical properties to a much lesser degree than observed for other derivatives as oxalate, succinate, or CT [ 35 , 54 , 55 ]. Significant structural and morphological changes were observed at concentrations above 2 mol% in contrast to tocopherol derivatives, where membrane disordering was observed even at 1 mol% concentration.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In DSC measurements, the increasing presence of tocopherols always led to broadening of ΔT 1/2 , progressively decreasing T m and diminishing ΔH m and cooperativity, together with the simultaneously formed new bands, thus indicating that the structural changes in the liposomes were induced by the presence of tocopherols, leading to a fluidization process at lower temperatures. Our studies in DPPC have shown that the presence of α-T at low concentration affects the membrane’s physicochemical properties to a much lesser degree than observed for other derivatives as oxalate, succinate, or CT [ 35 , 54 , 55 ]. Significant structural and morphological changes were observed at concentrations above 2 mol% in contrast to tocopherol derivatives, where membrane disordering was observed even at 1 mol% concentration.…”
Section: Discussionmentioning
confidence: 86%
“…DPH studies for investigated derivatives showed that membrane disordering follows increasing concentrations, whereas, in the case of α-T, the membrane structure eroded slowly and significant fluidization occurred at 20 mol%. Furthermore, in the case of α-T [ 35 ] and CT, we noticed increasing ordering in the liquid crystalline phase, whereas the ester derivatives showed the opposite effect, i.e., they introduced some disordering into the gel phase [ 35 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was used to study the thermal behavior of the liposome and DOX-encapsulated liposome samples. DSC strategy is utilized to determine the phase transition temperatures of liposomes [5]. The endothermic phase transition temperature of the liposomes and DOX-NP TM was found to be 55-61°C and 52°C, respectively Figure (3.3).…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…Liposomes may be defined simply as lipid (usually phospholipids) vesicles enclosing an aqueous space [3]. Liposomes are most frequently composed of phospholipids, particularly phosphatidylcholine, but may also include other lipids, such as egg phosphatidylethanolamine, when they are consistent with lipid bilayer structure [4,5]. A liposome design may employ surface ligands when attaching to unhealthy tissue [6].…”
Section: Introductionmentioning
confidence: 99%